PROBLEMS REGARDING THE OPERATION OF CONTROLLED LANDFILL IN TANJUNGPINANG - Zures Gustiabani; Seow Ta Wee (Fakultas Teknik, Universitas Riau Kepulauan, 2021)
A controlled landfill, which sits between open dumping and sanitary landfills, is one of the strategies to manage the waste produced. The single landfill in Tanjungpinang, Indonesia, is called Ganet Landfill.This landfill is now experiencing operating issues in addition to other environmental issues. This research is supposed to analyse the way of the controlled landfill operation, the function of controlled landfill and the problems regarding to the operation of the landfill. The case study was held at Ganet landfill in Tanjungpinang, Indonesia as a controlled landfill. This study used a qualitative approach and semi-structured interviewing tool. Four respondents from Ganet Landfill Office, the Department of Public Housing, and the People Settlement Riau Archipelago participated in the data gathering. Findings indicated that the most significant present issue at Ganet landfill is a shortage of heavy machinery, labor, future land, and infrastructure leading to unloading sites. Therefore, the discussion on the challenges faces in operating the controlled landfill, the advantages and disadvantages of using controlled landfill compared to sanitary landfills, and determination of the innovation and improvements on controlled landfill are expected to be given in the future.